Pengendali Persediaan Barang Menggunakan Metode Single Exponential Smothing untuk Peramalan Penjualan - Muhamad Taufik Ali; Alfa Bintang (SAFE-Network, 2022)
CV. Usaha Muda Materials is a company engaged in the distribution of wood, cement, iron and other building materials. Frequent errors in data collection of purchases and sales lead to disinformation in the distribution of goods. Prediction is a process for estimating how many needs in the future which include needs in terms of quantity, quality, time and location needed in order to meet the demand for goods or services. Prediction of the number of inventory items can be calculated using exponential smoothing, Exponential smoothing is often called Exponential Smoothing, exponential smoothing method is a prediction with a moving average technique where data weighting is weighted with an exponential function. The research methodology has steps that are used to solve problems that arise. The problems that occur in this study are regarding the prediction of CV. Young Business Materials using the Single Exponential Smoothing method. Prediction results are obtained by finding the constant value (alpha) with the smallest error using the Mean Squered Error (MSE), Root Mean Squred Error (RMSE), Mean Absolute Error (MAE) and Mean Absolute Percentage Error (MAPE) methods. The results of this study using Single Exponential Smothing have obtained predictions of 132 rods for January 2022. Based on the prediction accuracy test using the Mean Squered Error (MAE) method with a value of 3.01, Mean Squered Error (MSE) with a value of 18.18, and MAPE (Mean Absolute Percentage Error) obtained an error accuracy value of 9% using a weighted value of (alpha) 0.3. So this research can be taken into consideration for CV. Young Business Materials as an evaluation and appropriate decision making in order to minimize the risk of losses due to errors in the management of business capital.